Second Language Teaching and Research: Teachers’ Perspective - Amjad Ali Jokhio (JEELS (Journal of English Education and Linguistics Studies), 2022)
This study aims to know teachers’ perception regarding research and throw a shadow of light on this critical issue with respect to teaching pedagogy. For this study, data were collected through survey questionnaire with close ended items from 104 secondary school teachers (SSTs) (grade 6 to 10) and English language centers of Karachi. The data analysis revealed that most of the teachers believed that the knowledge they gain from the teaching is more effective and valuable rather than the knowledge acquired from research. In both categories, majority of the participants declared that they have limited sources available in order to access the Second Language Acquisition (SLA) articles, whereas half of them stated that they do not have enough time to conduct SLA research, a few of them reported as lack of interest, one of the SSTs indicated that research articles are difficult to understand and no ability to conduct research. Furthermore, majority of the teachers agreed that a teacher should be researcher, whereas a few of them disagreed with the statement. This study concludes with some ideas and proposals to remove the pertaining communication barriers between researchers and teachers.